Students’ Attitudes based on Adoption of Scientific Attitudes and Interested Expanding Time Learning Science - E. Erika; Edwin Kurniawan; Azizah Hanum (Universitas Pendidikan Mandalika, 2020)
The purpose of this research is to look at the description of scientific attitudes possessed by students at SMPN 17 jambi city based on indicators of adoption of scientific attitudes and indicators of interest in increasing the time of science learning. This research is a quantitative study in which researchers use survey methods with data collection techniques using a questionnaire. The results of the 2 attitude indicators discussed in this study are indicators of the adoption of scientific attitudes of 62.5% of students categorized as good. While the interest in increasing science learning time by 66.4% of students is of sufficient category. Based on the results of research that has been conducted it can be concluded that students have adopted a good scientific attitude and have sufficient interest to increase their science learning time.